Pengaruh Affiliate Marketing, Content Quality, dan Electronic Word of Mouth terhadap Purchase Decision Skincare Skintific oleh Gen Z pada TikTok Shop di Jabodetabek - Amanda Chrisanty Wibowo; Annisa Lutfia; Daru Putri Kusumaningtyas (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of Affiliate Marketing, content quality, and electronic word of mouth on purchase decision of Skintific skincare products by Generation Z on TikTok Shop in Jabodetabek. A quantitative approach with a survey method was employed in this study. The population was Generation Z residing in Jabodetabek who had purchased Skintific products through TikTok Shop. A sample of 200 respondents was selected using purposive sampling technique. Data were collected through a questionnaire with a six-point Likert scale. Data analysis techniques included validity test, reliability test, normality test, heteroscedasticity test, simple linear regression analysis, t-test, and coefficient of determination test using IBM SPSS Statistics version 25. The results showed that Affiliate Marketing had a positive and significant effect on purchase decision (sig. 0.000; R² 22.1%), content quality had a positive and significant effect (sig. 0.000; R² 13.1%), and electronic word of mouth had a positive and significant effect (sig. 0.000; R² 26.2%). It can be concluded that all three variables have a positive and significant effect on purchase decision of Skintific products by Generation Z on TikTok Shop in Jabodetabek, with electronic word of mouth providing the greatest contribution.